A Concise Total Synthesis of (+)‐Paniculatine. Issue 15 (28th May 2019) - Liu, Jian; Chen, Sheng; Li, Ningning; Qiu, Fayang G.
Abstract: The total synthesis of (+)‐paniculatine, a unique structure in Lycopodium alkaloids, has been achieved starting from two known intermediates. The efficiency of the present synthesis depends on a few key elements including Hosomi‐Sakurai allylation and an unusual intramolecular Michael addition of an enolate to an unsaturated amide. Abstract :